Problems and Prospects of Transport Development in Samarkand (Global Scientific Review, 2022)
Despite the large scale of street construction and repair work in Samarkand, there are many problems and shortcomings. It is no secret that today most of the public roads in our city have been repaired. Due to the failure of some busy streets, traffic safety requirements are violated and various accidents occur. Rough, dilapidated streets can be cited as many examples as you want. The increase in the number of cars in urban areas is causing congestion and inconvenience on the roads